Clarifying the effect of a small amount of Cr content on the corrosion of Ni-Mo steel in tropical marine atmospheric environment. (January 2023) - Dong, Baojun; Liu, Wei; Zhang, Tianyi; Chen, Longjun; Fan, Yueming; Zhao, Yonggang; Li, Hai; Yang, Weijian; Sun, Yipu
Abstract: The effect of Cr content on the corrosion behavior of Ni-Mo steel in the tropical marine atmospheric environment is systematically investigated. The increase of Cr content accelerates the aggregation and the enrichment of Ni element, and thus promotes the formation of an inner electronegative film which attracts positively charged ions including Mo 6+, Mo 4+, Ni 2+ and Cr 3+ ions, and repels negatively charged Cl - ions. Cr promotes the formation of more nano-FeOOH and the conversion of γ-FeOOH into α-FeOOH. A small amount of chromium promotes the formation of micro-pits at the initial stage, and with time, those micro-pits gradually accumulate into pieces. Highlights: Adding a small amount of Cr into Ni-Mo steel reduces the corrosion rate. An electronegative inner film composed of Cr and Ni elements attracts Mo 6+, Mo 4+, Ni 2+ and Cr 3+ ions, and repels Cl - ions. Cr2 O3 acts as the nucleation site of FeOOH, generating more nano FeOOH, and doping Cr promotes the transformation of γ-FeOOH to α-FeOOH.